New butenolide derivatives from the marine sponge-derived fungus Aspergillus terreus. Issue 3 (1st February 2018) - Sun, Yating; Liu, Jingtang; Li, Lei; Gong, Chi; Wang, Shuping; Yang, Fan; Hua, Huiming; Lin, Houwen
Graphical abstract: Abstract: Two new butenolide derivatives (±)-asperteretal D ((± )-1 ) and asperteretal E (2 ) containing rare 2-benzyl-3-phenyl substituted lactone core, together with nine known analogues (3 –11 ) were obtained from a fungus Aspergillus terreus derived from the marine sponge Phakellia fusca . All the structures were elucidated on the basis of extensive NMR spectroscopic data. The chiral chromatography analyses allowed the separation of the (±)-asperteretal D, of which the absolute configurations were determined by comparing the experimental to calculated electronic circular dichroic (ECD) spectra. Compounds(±)-1, 2 –5, and7 exhibited potent inhibitory activities against α -glucosidase with IC50 values ranging from 8.65 to 20.3 µM (positive control acarbose with an IC50 value of 320 µM). In addition, derivatives5 –8 also showed moderate antioxidant activities.